Sculptures on the interior surface of the enclosure walls - Temples of India Project Team (Jio Institute, 2024)
The interior surface of the enclosure walls, similar to the entrances, features several sculptures such as Brahma, Vishnu, and Mahesha, dikapalas (deities of cardinal directions), surasundaris (celestial maidens), and vyalas (composite mythical creatures).